PENGEMBANGAN PAKET WISATA DANAU BIRU KARANG SIDEMEN KABUPATEN LOMBOK TENGAH - Yoby Arya Wilantara; Komang Mahawira; Achlan Fahlevi Royanow (Juremi: Jurnal Riset Ekonomi, 2024)
The aim of this research is to develop a tour package for the Blue Lake, Karang Sidemen, Central Lombok Regency, West Nusa Tenggara. This research uses descriptive qualitative research methods, namely techniques for collecting data and in-depth understanding, with the data collection process through observation, interviews, documentation. Data was obtained through interviews from several informants, namely the Village Head, Bumdes, and Pokdarwis to find out the development of tour packages at Lake Biru. This research is very important to know the development of tour packages at Blue Lake and as a reference regarding the development of Blue Lake Tour Packages, Karang Sidemen, Central Lombok Regency